1977
DOI: 10.1029/ja082i022p03324
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an ionospheric acceleration mechanism producing energetic (keV) ions primarily normal to the geomagnetic field direction

Abstract: 0+ ions with energies of approximately 1 keV have been observed flowing upward out of the ionosphere with a pitch angle distribution having a minimum along the magnetic field direction and maxima in about the 130°–140° range. The measurements were obtained with an energetic ion mass spectrometer experiment on the satellite 1976‐65B at an altitude of about 7600 km in the northern dayside polar cusp. The data are interpreted as resulting from a mechanism which accelerates ambient ionospheric ions in a direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
142
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(150 citation statements)
references
References 3 publications
6
142
0
Order By: Relevance
“…Acceleration from magnetic field-aligned potential drops is known to occur at several 1000 km altitudes above auroral arcs (e.g., Mozer et al 1977;Sharp, Johnson, & Shelley 1977;Gorney et al 1981). It is thus the closest realization of a powerful cosmic acceleration process, easy to probe, and, indeed, documented by a wealth of data (a good collection of papers with data from the Swedish Viking satellite can be found in the May issue [no.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration from magnetic field-aligned potential drops is known to occur at several 1000 km altitudes above auroral arcs (e.g., Mozer et al 1977;Sharp, Johnson, & Shelley 1977;Gorney et al 1981). It is thus the closest realization of a powerful cosmic acceleration process, easy to probe, and, indeed, documented by a wealth of data (a good collection of papers with data from the Swedish Viking satellite can be found in the May issue [no.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for perpendicular ion acceleration (ion conics) has been accumulated from at least four magnetospheric satellites and two sounding rockets (Shelley et al, 1976;Sharp et al, 1977;Klumpar, 1979;Horwitz, 1980;Whalen et al, 1978, Yau et al, 1982. In contrast there exists scant evidence for the mechanism that produces perpendicular ion acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that electrostatic ion-cyclotron waves may be responsible for the production of ion conics [Sharp, 1977], energetic (keV) HI and 0* ions having pitch-angle distributions peaked at an angle to the magnetic field. Ions may be heated in the direction perpendicular to the magnetic field (transverse acceleration) [Ungstrup et al, 19791 in the presence of ion-cyclotron waves, and subsequently flow upward under the magnetic mirror force producing ion beams or conics.…”
Section: [-mentioning
confidence: 99%